Pengaruh Kompetensi Komite Audit, Gender dan Laba Rugi terhadap Audit Report Lag: Studi Empiris pada Perusahaan yang Terlambat Menyampaikan Laporan Keuangan Auditan ke Bursa Efek Indonesia (BEI) pada tahun 2018-2022 - Endang Sri Astuti; Nelvirita Nelvirita (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of audit committee competence, gender, and profit and loss on audit report lag. This study uses annual report data for all companies that are late in submitting audited financial reports to the Indonesia Stock Exchange (IDX) for 2018-2022. The sampling technique used in this research is purposive sampling, with a total sample of 333 companies in 2018-2022. This study uses multiple linear regression analysis in hypothesis testing. The results showed that audit committee competence had a negative and insignificant effect on audit report lag, female gender had a positive and insignificant effect on audit report lag, and companies with shorter profits experience shorter audit report lag than those incurring losses.